2014
DOI: 10.1038/ncb3060
|View full text |Cite
|
Sign up to set email alerts
|

Kinetochore motors drive congression of peripheral polar chromosomes by overcoming random arm-ejection forces

Abstract: Accurate chromosome segregation during cell division in metazoans relies on proper chromosome congression at the equator. Chromosome congression is achieved after bi-orientation to both spindle poles shortly after nuclear envelope breakdown, or by the coordinated action of motor proteins that slide misaligned chromosomes along pre-existing spindle microtubules. These proteins include the minus-end-directed kinetochore motor dynein, and the plus-end-directed motors CENP-E at kinetochores and chromokinesins on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
271
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 142 publications
(289 citation statements)
references
References 48 publications
18
271
0
Order By: Relevance
“…By backtracking these polar chromosomes to their original positions at NEB, we found that they initially occupied a peripheral region outside the interpolar spindle ellipsoid, and were always significantly closer to one of the poles. 5 In contrast, chromosomes that were already positioned in the interpolar region at NEB were easily accessible by microtubules from both spindle poles and became bi-oriented soon after NEB. Importantly, these chromosomes completed alignment in the absence of all 3 motor activities.…”
Section: Congression Of Peripheral Chromosomes Depends On Motor Proteinsmentioning
confidence: 99%
See 4 more Smart Citations
“…By backtracking these polar chromosomes to their original positions at NEB, we found that they initially occupied a peripheral region outside the interpolar spindle ellipsoid, and were always significantly closer to one of the poles. 5 In contrast, chromosomes that were already positioned in the interpolar region at NEB were easily accessible by microtubules from both spindle poles and became bi-oriented soon after NEB. Importantly, these chromosomes completed alignment in the absence of all 3 motor activities.…”
Section: Congression Of Peripheral Chromosomes Depends On Motor Proteinsmentioning
confidence: 99%
“…Importantly, these chromosomes completed alignment in the absence of all 3 motor activities. 5 Thus, we concluded thatonly peripheral chromosomes that cannot bi-orient soon after NEB require motor proteins to congress.…”
Section: Congression Of Peripheral Chromosomes Depends On Motor Proteinsmentioning
confidence: 99%
See 3 more Smart Citations